Chitonaster johannae Koehler 1908 ... - Mah, Christopher L. (Zenodo, 2011)
Chitonaster johannae Koehler, 1908 (Figures 6 A–G) Koehler, 1907: 144; 1908: 542; A.M. Clark, 1993: 250; (as C. johannae Koehler, 1907 ) Distribution. South of South Orkney, South Georgia Islands, and Elephant Islands, 2856–4204 m. Distinctions from other species. Chitonaster johannae is herein restricted to those Chitonaster with valvate pedicellariae, abactinal arm plates in transverse series, with clustered spines on abactinal and superomarginal spines with relatively small abactinal plates, and lacking papulae. All C. johannae examined with these characters, including Koehler’s (1908) original description are apparently restricted to abyssal depths (> 2856 m). Shallowwater specimens, including those referred to C. johannae by Mein (1992) and Stampanato and Jangoux (1993), are referred to C. trangae n. sp. Comments on type material. MNHN EcAh 3511 is herein designated as the lectotype from Koehler’s (1908) syntype series. It corresponds in nearly ever regard to one specimen, with R=23.0 mm, indicated ... : Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on pages 15-17, DOI: 10.5281/zenodo.276783 ...